Parascreen as an alternative diagnostic tool for falciparum malaria - Jenny Ginting; Siska Mayasari; Munar Lubis; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 2008)
Background Malaria is a parasitic disease with high morbidityand mortality. Rapid immunochromatographic are emerging todetect specific antigens of human plasmodia.Objective To determine the sensitivity and specificity ofParascreenfor the detection of Plasmodium falciparum in children.Methods A diagnostic test study was performed in MandailingNatal District, Penyabungan, North Sumatera. Subjects werepublic health center and hospital patients with symptoms of fever,pallor, headache, and diarrhea. Blood specimens were obtained forParascreen testing. Microscopy of Giemsa-stained blood samplesserved as the gold standard.Results One hundred and four subjects were studied. The sensitiv-ity and specificity ofParascreen were 76% and 100%, respectively.Positive and negative predictive values of the test were 100% and49%, respectively. Likelihood ratio was infinite for a positive testand 0.23% for a negative test.Conclusion Parascreen is a useful and highly specific di-agnostic tool for P. falciparum malaria